Using the bottom-up and outside-in sequence for panfacial fracture management: Does it provide a clinical significance? - De Melo, Willian Morais [UNESP]; Sonoda, Celso Koogi [UNESP]; Shinohara, Elio Hitoshi [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (Wolters Kluwer, 2013)
Panfacial fractures usually refer to simultaneous facial fractures, which affect the upper, middle, and lower thirds of the face. The management of panfacial fracture is complex because of the lack of reliable landmarks. Literature has shown many approaches for management of panfacial fractures. Every segment of bone has a precise function in the repair. Therefore, the bottom-up and outside-in sequence is the most widely used approach in the management of panfacial fractures. These facial fractures present remarkable challenges for both experienced and inexperienced surgeons. This article aimed to report a case of a panfacial fracture (mandibular condylar and symphysis fractures associated with an atypical Le Fort III fracture) in a 48-year-old man. The patient was successfully treated using bottom-up and outside-in sequence by accessing all facial injuries. Postoperatively, radiograph examination revealed good reduction and fixation of titanium plates, and physical examination revealed good functional and esthetic outcomes. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Condylar fracture; Mini-retromandibular; Open reduction; Panfacial fracture; Rigid fixation; Subtarsal